Evaluation and analysis of methane adsorption capacity in deep‐buried coal seams. Issue 3 (26th April 2022) - Zheng, Yuannan; Jiang, Bingyou; Ren, Bo; Lin, Hanyi; Tao, Wenhan; Wang, Shijv
Abstract: In this work, the high‐pressure methane adsorption/desorption tests were conducted in four coal samples (from low‐rank bituminous coal to anthracite) under different temperature and pressure conditions to reveal the mechanism of desorption hysteresis effect in the deep‐buried coal seams. The experimental and fitting results show that the presence of free methane molecules in the adsorption phase results in an obvious difference between the measured methane adsorption amount with the actual adsorption capacity. The Langmuir, Langmuir–Freundlich (L–F) and Dubinin–Astakhov (D–A) models have their own advantages and disadvantages in fitting the experimental adsorption/desorption data. As residual adsorption capacity C fitted by the D–A model would be negative at high temperatures and lose the meaning of the constant, the Langmuir model is more suitable to describe methane desorption process. The residual adsorption capacity fitted by Langmuir model tended to decrease as the temperature increased until it is almost completely desorbed at 373 K. Meanwhile, because the adsorption sites with lower energy are gradually occupied by methane molecules in the high‐pressure stage, intermolecular forces increased and methane molecules are more easily desorbed. Therefore, the desorption hysteresis coefficient trends to increase exponentially with the decrease of pressure and temperature, which indicated that the original gas content of the coal seams may decrease with the increase of the burial depth, but the risk of coal and gas outburst accidents may increase. © 2022 Society of Chemical Industry and John Wiley & Sons, Ltd.